Novel uranyl(VI) complexes incorporating ethynyl groups as potential halide chemosensors: an experimental and computational approach. Issue 11 (2nd November 2017) - Bartocci, Silvia; Sabaté, Ferran; Yafteh Mihan, Francesco; Bosque, Ramon; Rodríguez, Laura; Dalla Cort, Antonella
Abstract: The synthesis of two novel Uranyl-salophen complexes, 1 and2, decorated with ethynyl substituents, and the study in chloroform of their binding properties toward three different tetrabutylammonium halide salts, i.e. fluoride, chloride, bromide, are here reported. Such derivatives proved to be efficient halide receptors. The presence of two ethynyl groups in the para position, with respect to the phenoxide oxygens, seemed to be accountable for the moderate emission shown by complex1 . Surprisingly, instead, complex2 does not show such property. The possibility of1 to form dimers in non-coordinating solvents provides an explanation for such difference, since emission can be induced by the aggregation. This finding provides an unprecedented example of aggregation induced emission (AIE) for metal salophen derivatives. Moreover DFT calculations provide theoretical insight to the formation of host-guest complexes. Their stabilities were calculated in vacuum and in chloroform and the results are perfectly in agreement with the experimental data. Abstract :